Dutch and Flemish flower pieces : paintings, drawings and prints up to the nineteenth century - Segal, Sam; Alen, Klara, 1988- (Brill / Hes & De Graaf, 2020)
This richly illustrated book provides an overview of all known Dutch and Flemish artists up to the nineteenth century who painted or drew flower pieces, or else made prints of them. Unlike many mainstream art historical studies, the book takes a truly comprehensive approach, including cases where only a single example is known or even if nothing of the artist's other work appears to have survived. Containing highly instructive lists identifying the names of flowers, as well as insects and other animals, the book also discusses the earliest depictions of flower still life and the distinctive characteristics behind the development of floral arrangements in different periods, including the variation of the flowers, the variety of techniques used by artists, as well as an exploration of the symbolism behind the numerous plant and animal species this form of art portrays. Composed in Dutch, the text was translated into English by Judith Deitch and edited by Philip Kelleway.